Community Empowerment through Training on Production and Packaging of Instant Red Ginger (Zingiber officinale var. Rubrum) in Lamedai Village, Kolaka - Yermia; Juniaty Arruan Bulawan (Teras Kampus as a member of PT Palem Edukasi Nusantara, 2026)
This community service activity aims to provide training on making instant red ginger to the people of Lamedai Village, Tanggetada District, Kolaka Regency. The method used was direct training involving 19 participants from Harapan Baru Church. The training included the introduction of red ginger benefits, processing techniques into instant form, and simple packaging methods. The results showed that participants were able to produce instant red ginger using simple tools and local ingredients. The activity received a positive response, as seen from the high enthusiasm and active involvement of participants. This training is expected to increase the economic value of ginger, extend its shelf life, and improve the community's income. The participants also gained knowledge about packaging design and business licensing procedures (P-IRT).